2016
DOI: 10.1371/journal.pone.0151712
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aroma Foot Massage on Blood Pressure and Anxiety in Japanese Community-Dwelling Men and Women: A Crossover Randomized Controlled Trial

Abstract: ObjectivesThe aim of this study was to investigate the effects of aroma foot massage on blood pressure, anxiety, and health-related quality of life (QOL) in Japanese community-dwelling men and women using a crossover randomized controlled trial.MethodsFifty-seven eligible participants (5 men and 52 women) aged 27 to 72 were randomly divided into 2 intervention groups (group A: n = 29; group B: n = 28) to participate in aroma foot massages 12 times during the 4-week intervention period. Systolic and diastolic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
4
21
1
8
Order By: Relevance
“…Eguchi et al, study was conducted on Japanese men and women; the findings of this study showed that massage therapy could reduce anxiety and improve quality of life. However, this reduction in anxiety was not significant, unlike the present study according to which reflexology resulted in a significant reduction in anxiety 16 . The results of Peng et al, study (2015) showed that massage led to anxiety reduction in cardiovascular patients prior to invasive procedures, which turned out to be consistent with the findings of the present study 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…Eguchi et al, study was conducted on Japanese men and women; the findings of this study showed that massage therapy could reduce anxiety and improve quality of life. However, this reduction in anxiety was not significant, unlike the present study according to which reflexology resulted in a significant reduction in anxiety 16 . The results of Peng et al, study (2015) showed that massage led to anxiety reduction in cardiovascular patients prior to invasive procedures, which turned out to be consistent with the findings of the present study 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, changes in BP were seen in those participants with reduced anxiety and depression after the intervention. As other studies also indicated that BP was decreased with the reduction of anxiety, it was believed that aroma foot massage might reduce BP through reducing the participant's anxiety (Eguchi et al, ). In addition, other studies also reported the decreased levels of SBP, DBP, and MBP after aroma self‐foot reflexology massage (Bahrami, Rejeh, Heravi Karimooi, Tadrisi, & Amin, ; Hur et al, ; Kim & Kim, ).…”
Section: Discussionmentioning
confidence: 94%
“…Another potential selection bias may have been caused by the possible overlap of agitation and anxiety. While some evidence has been found in the literature regarding the effectiveness of CAM therapies in anxious states (Salach, 2006;Eguchi et al, 2016;Strauss et al, 2014), these therapies may actually treat the "agitated" clinical features of anxiety. Such therapies should be redefined as "anti-agitation" instead of "anti-anxiety" in order to be included in our study.…”
Section: Assessment Of the Robustness Of The Reviewmentioning
confidence: 99%
“…Considering the prevalence of delirium and agitation among older persons and the limitations of standard care for these conditions, we propose examining whether CAM techniques may play a safe and effective role in this setting. Because CAM therapies are often used to treat mental/emotional disturbances (Deng and Wang 2016;Eguchi et al, 2016;Avisar et al, 2012;Zeng et al, 2013;Zhang et al, 2015;Rodriguez-Mansilla et al, 2015), we assumed they may be considered in treating agitation and delirium in older persons. We therefore chose to carry out a systematic assessment of the impact and mechanisms of action of both pharmacological and non-pharmacological CAM therapies in treating agitation and delirium.…”
Section: Introductionmentioning
confidence: 99%